ANALISIS DATA RATE DAN INTERFERENSI WI-FI PADA VIDEO STREAMING MELALUI JARINGAN BLUETOOTH PICONET PERVASIVE - Hasad, Andi; Paronda, Abdul Hafid (JREC (Journal of Electrical and Electronics), 2015)
The objective of this research is to develop a piconet pervasive system that meets the Cisco standard for QoS video streaming value of the throughput, delay, jitter and packet loss, by performing the optimization and analysis of video streaming on the network, by utilizing the bluetooth cell phones and computers media in an condition which have Wi-Fi or do not have Wi-Fi. The stages of research are analysis of bluetooth network system, design a prototype system, audio video compression, hint track, optimization, system testing, performance measurement, and analysis of measurement results. The results showed packet loss value for all video compression on a client-server distance of 2.5 m, 5 m, 7.5 m and 10 m has been fulfilling the Cisco standard of QoS video streaming, where the smallest value obtained at 8 kbps data rate of 2.12% packet loss to an condition that does not have Wi-Fi, and a distance of client - server 2.5 m. In condition that have Wi-Fi interference, the largest value obtained at 24 kbps data rate of 4.62% packet loss to an condition that have a distance of client - server 10 m. This value is still appropriate of Cisco QoS standards streaming video that sets the value of the largest packet loss is 5%. Delay parameters have values ranged from 0.43 - 1.81 milliseconds, while the standard of maximum delay for QoS video streaming is 5 seconds.Keywords: video streaming, bluetooth, QoS, optimization, Wi-Fi interference. Piconet Pervasive